2021
DOI: 10.1002/pchj.482
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of empathy: Meta‐analysis evidence of the relationship between empathy and depression

Abstract: Regardless of a large amount of literature, whether empathy closely relates to depression is far from conclusive. The present study collected previous evidence and performed a meta-analysis to investigate the correlation between empathy and depression. By searching databases, 21 studies and 48 effect sizes were collected. Results showed that empathy was not correlated to depression (r = .006, p = .87). However, subgroup analyses showed that while the relationship between affective empathy and depression was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 72 publications
3
34
0
Order By: Relevance
“…Specifically, when the level of attentional shift was low, the relationship between cognitive empathy and depression was no longer significant. When the level of individual attentional shift was high, the negative correlation between cognitive empathy and depression is significant, which is also consistent with previous research results, that is, in some studies, cognitive empathy and depression showed significantly negative correlation (Bennik et al, 2019) or not significantly correlated (Yan et al, 2021).…”
Section: Attentional Shift Not Focus Moderated the Relationship Betwe...supporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, when the level of attentional shift was low, the relationship between cognitive empathy and depression was no longer significant. When the level of individual attentional shift was high, the negative correlation between cognitive empathy and depression is significant, which is also consistent with previous research results, that is, in some studies, cognitive empathy and depression showed significantly negative correlation (Bennik et al, 2019) or not significantly correlated (Yan et al, 2021).…”
Section: Attentional Shift Not Focus Moderated the Relationship Betwe...supporting
confidence: 91%
“…Existing findings on the relationship between depression and empathy was inconsistent. For example, although cognitive empathy was generally thought to be negatively associated with depression ( Bennik et al, 2019 ), some empirical studies failed to find the asserted association ( Yan et al, 2021 ). Similarly, some studies found the positive association of emotional empathy and depression ( Bennik et al, 2019 ) while others found negative associations ( Chen et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In all these five facets, the differences between Cluster 1 and Cluster 2 were not significant. In light of previous studies, it seems that mood disorders symptoms relate to impairments in self-direction as well as in empathy (especially affective empathy) [ 54 56 ]. Mood disorders also relate to the ability for reciprocal cooperation (the Mutuality facet from the Intimacy element) [ 57 ].…”
Section: Discussionmentioning
confidence: 93%
“…In the self-evaluation, the introversion trait was the most frequent; 50% of the patients did not feel at ease with themselves and 42% were dissatisfied with their school environment, but they did have high levels of empathy. Previous studies have shown that personality traits such as introversion and empathy are risk factors for mental disorder development [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%